The Role of Circadian Rhythms in Muscular and Osseous Physiology and Their Regulation by Nutrition and Exercise - Aoyama, Shinya; Shibata, Shigenobu (Frontiers in Neuroscience, 2017)
The mammalian circadian clock regulates the day and night cycles of various physiological functions. The circadian clock system consists of a central clock in the suprachiasmatic nucleus (SCN) of the hypothalamus and peripheral clocks in peripheral tissues. According to the results of circadian transcriptomic studies in several tissues, the majority of rhythmic genes are expressed in a tissue-specific manner and are influenced by tissue-specific circadian rhythms. Here we review the diurnal variations of musculoskeletal functions and discuss the impact of the circadian clock on homeostasis in skeletal muscle and bone. Peripheral clocks are controlled by not only photic stimulation from the central clock in the SCN but also by external cues, such as feeding and exercise. In this review, we discuss the effects of feeding and exercise on the circadian clock and diurnal variation of musculoskeletal functions. We also discuss the therapeutic potential of chrono-nutrition and chrono-exercise on circadian disturbances and the failure of homeostasis in skeletal muscle and bone.